2011
DOI: 10.1089/ten.tea.2010.0338
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation and Neovascularization Mediated by Mesenchymal Stem Cells and Endothelial Cells in Critical-Sized Calvarial Defects

Abstract: Bone represents a highly dynamic tissue whose development is strongly dependent on vasculogenic and angiogenic processes. Neovascularization also plays an important role in fracture healing and in tissue engineering applications aiming at restoring bone function. We have previously shown in a heterotopic subcutaneous implantation model of severe combined immunodeficiency (SCID) mice that implanted human umbilical vein endothelial cells (HUVECs) gave rise to the formation of a complex functional human neovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 49 publications
4
94
0
Order By: Relevance
“…In contrast to our suggested mechanism of paracrine signaling, several other groups failed to show osteogenic enhancement when MSCs were cultured in the CM of ECs [40], instead suggesting direct cell-cell contact via gap junction communication was required to mediate the osteogenic enhancement effect [21,41]. These groups, however, used mature human ECs in coculture with osteoblast-like cells, which although they have shown promise in generating a prevascularized network [15,23] and/or enhancing osteogenesis [20,21,[40][41][42][43], their biological phenotype depends upon the site of the endothelium from which they were harvested from [44].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In contrast to our suggested mechanism of paracrine signaling, several other groups failed to show osteogenic enhancement when MSCs were cultured in the CM of ECs [40], instead suggesting direct cell-cell contact via gap junction communication was required to mediate the osteogenic enhancement effect [21,41]. These groups, however, used mature human ECs in coculture with osteoblast-like cells, which although they have shown promise in generating a prevascularized network [15,23] and/or enhancing osteogenesis [20,21,[40][41][42][43], their biological phenotype depends upon the site of the endothelium from which they were harvested from [44].…”
Section: Discussionmentioning
confidence: 57%
“…However, the majority of studies used ECs [19][20][21][22][23] rather than ECFC. In this project, well-characterized UCB-ECFC were cocultured with hfMSC [7] chosen primarily for their ability to undergo a well-defined osteogenic differentiation pathway [7,24,25] and superiority in osteogenic differentiation over adult counterparts [7,25] for bone tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…44 The bone defects were repaired with one of the following treatments: autologous bone, b-tri- 45 In addition to the enhanced vascularization demonstrated with the coimplantation of EPCs and MSCs, it is thought that coimplantation leads to MSCs acting as perivascular mural cells. 57 When cocultured with EPCs, MSCs have also shown a committed differentiation toward smooth muscle cell and pericyte phenotypes. 58 Differentiation appeared to occur due to direct cell-to-cell contact and extracellular signal-regulated kinase signaling, demonstrating the various pathways influencing the reciprocal interactions between EPCs and MSCs.…”
Section: Interactions With Epcsmentioning
confidence: 99%
“…The authors postulated that endogenous neovascularization in the defects may have been sufficient to sustain osteogenesis. 112 Nair et al 113 cultured BMSCs on bare or fibrin-coated bioactive ceramics made of hydroxyapatite (HA) and silicacoated HA cylinders for up to 28 days. Analysis of cell viability, morphology, proliferation, cell cycle assay, and differentiation showed that the fibrin considerably enhanced cellular functions.…”
mentioning
confidence: 99%